Host suitability of peppers to the false root-knot nematode Nacobbus aberrans - Lax, Paola (2016)
The false root-knot nematode, Nacobbus aberrans, causes severe damage to field and greenhouse pepper crops in several localities of the American continent. No commercial peppers (Capsicum annuum) resistant to this nematode are available up to the present. Host suitability of 6 experimental and 3 commercial peppers (some of them carrying Me1 and Me7 resistance genes to Meloidogyne spp.) to two N. aberrans populations were evaluated under greenhouse experiments. None of the peppers was found to be resistant to the nematode. The evaluated parameters exhibited significant differences among some peppers tested within a single population and between populations for a single plant material. Some peppers carrying resistance showed higher nematode reproduction than some lines that did not possess resistance genes. These results confirmed that the genes conferring resistance to Meloidogyne spp. do not provide protection against this species of root-galling nematode. Host suitability of pepper lines carrying Me1 or Me7 resistance genes against N. aberrans is evaluated for the first time. Search for resistant genes against this nematode in wild peppers growing in areas where this nematode is indigenous should be promoted.